PENGEMBANGAN BAHAN AJAR TEMATIK TERPADU BERBASIS MODEL DISCOVERY LEARNING di KELAS IV SD NEGERI 030 PALEMBANG - Triyana Yetra (Jurnal Buah Hati, 2019)
The type of research used is the development research using 4-D model consisting of 4 stages, namely: defining (define), design, development and disseminate. The disseminate stage is performed on a limited scale. The developed teaching materials are validated by experts in language, content, and design. Then integrated thematic materials are experimented to see the practicality and effectiveness of thematic integrated teaching materials. The practicality of teaching material is seen from questionnaire of teacher and student response, effectiveness seen from activity observation and student learning result in using integrated thematic material based on Discovery Learning model. The results obtained, validation of learning materials obtained 3.6 with the category is very valid. At the stage of practicality, the results obtained that the teaching materials are practical to use. The use of teaching materials can improve student activities and learning outcomes. Student achievement completeness reaches 83%. This means that teaching materials are effective in improving student learning outcomes. From the research result, it is found that the developed teaching material has been valid, practical and effective as one of the teaching materials in the fourth grade of elementary school. Abstrak Jenis penelitian yang digunakan adalah penelitian pengembangan dengan menggunakan model 4-D yang terdiri dari 4 tahap yaitu: tahap pendefinisian (define), perancangan (design), pengembangan (develop) dan penyebaran (disseminate). Tahap disseminate dilakukan pada skala terbatas. Rancangan yang telah didesain kemudian divalidasi oleh 3 orang ahli. Kepraktisan dilihat melalui hasil analisis angket respon siswa dan guru. Keefektifan dilihat melalui hasil analisis observasi aktivitas dan hasil belajar siswa. Hasil yang diperoleh, validasi bahan ajar diperoleh rata-rata 3,6 dengan kategori sangat valid. Pada tahap praktikalitas, diperoleh hasil bahwa bahan ajar sudah praktis untuk digunakan. Penggunaan bahan ajar dapat meningkatkan aktivitas dan hasil belajar siswa. Tingkat ketuntasan hasil belajar siswa mencapai 83%. Ini berarti bahan ajar efektif dalam meningkatkan hasil belajar siswa. Dari hasil penelitian diperoleh bahwa bahan ajar yang dikembangkan telah valid, praktis dan efektif digunakan sebagai salah satu bahan ajar di kelas IV sekolah Dasar. Kata Kunci: Bahan ajar, pembelajaran integrasi, discovery learning model, model 4-D